EMPLOYERS' ASSESSMENT OFADEQUACYOFOFFICE TECHNOLOGY A N D M A N A G E M E N T C U R R I C U L U M F O R G R A D U AT E S EMPLOYABILITYSKILLSACQUISITIONINNORTH-WESTNIGERIA (NAU Journal of Technology and Vocational Education, 2024)
The study assessment of adequacy of office technology and management curriculum relativeto employment requirements in North-West Nigeria was necessitated by the need to ensurethat the products perform satisfactorily in employment. Two research questions guided thestudy and two null hypotheses were tested at 0.05 level of significance. Ex-post facto andsurvey research design were used forthe study. Population of 456 principal officers of publicand private establishments in North-West Nigeria wasstudied without sampling. Forty Ninequestionnaire items relating to adequacy of contents of Information and CommunicationTechnology and records management course units were developed and validated by panel ofexperts. The internal consistency reliability co-efficient of the instrument was establishedusing Pearson Product Moment Correlation Co-efficient and the overall reliability of theinstrument was established using K.R-20 formula. The internal consistency reliability coefficient obtained were 0.97 and 0.95respectively for the two clusters with the overallreliability co-efficient of 0.96. Mean and standard deviation were used to analyze data inrelation to the research questions while ztest was used to test the null hypotheses. Thefindingsrevealed that Office Technology and Management curriculum was adequate forICTand records management content for employability skills acquisition of the graduates.Furthermore, the respondents differed significantly in their mean ratings of adequacy ofOTM curriculum on ICT and records management. Based on the above findings it isrecommended among others that employers of labour, particularly Federal and StatesDepartment of Establishment and Training/Offices of Head of Service and Representativesof private establishmentsshould be co-opted in the future reviewof OTM curriculum.